Dendritic mixed hexakisadducts of C60 with a T(h) symmetrical addition pattern - Herzog, Andrea; Hirsch, Andreas; Vostrowsky, Otto (European Journal of Organic Chemistry, 2000)
The synthesis and complete characterization of dendritic hexakisadducts 8-13 of C with a mixed (1:5, 2:4, 3:3 and 4:2) T(h) symmetrical addition pattern is described. Pentakis-, tetrakis-, tris- and bisadducts 4-7 of C with diethyl malonate addends arranged in an incomplete octahedral addition pattern served as core building blocks. Completion of the pseudo-octahedral architecture was achieved by exhaustive cyclopropanation with first- to third-generation bromomalonate dendra 1-3 consisting of the corresponding Frechet-type 3,5-dihydroxybenzyl alcohol subunits. This concept allows for the convergent synthesis of globular dendrimers with a variable number of dendritic malonates (1-4) and a high dendron density in good yields. The H and C NMR spectra reflect the T(h) symmetrical addition pattern of the products and reveal spatial interactions of inner dendron branches.